Modern homosexualities : fragments of lesbian and gay experience - Plummer, Kenneth (Routledge, 1992)
These original essays, by both activists and academics, document and analyse the dramatic changes in lesbian and gay experience over the last twenty years. This book heralds a new maturity for lesbian and gay studies.